Managing Maritime Fieldwork Practices: A POAC Framework for Enhancing Student Competence in Indonesian Vocational Schools - Dwi Puspita Sari; Manap Somantri; Muhammad Kristiawan (PPSDP International Journal of Education, 2026)
This study aims to analyze the management of Field Work Practice (PKL) in enhancing the competence of Maritime Department students at State Vocational High School 4 Bengkulu City. A descriptive qualitative design was employed through interviews, observations, and document analysis involving school administrators, teachers, students, and industry partners. The study revealed that PKL management was systematically implemented through four key functions planning, organizing, actuating, and controlling. Collaborative planning aligned educational goals with industry needs, while dual supervision and continuous monitoring improved students’ technical competence and professional discipline. The results demonstrate that adaptive management practices supported by digital supervision enhance the effectiveness of vocational training in maritime settings. The novelty of this study lies in applying the POAC management model to maritime vocational education with limited communication environments. This research contributes by proposing an adaptive framework that strengthens Industry–School Partnerships and bridges the gap between vocational education and the maritime industry.